2023
DOI: 10.1101/2023.01.16.524187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitroproduction of cat-restrictedToxoplasmapre-sexual stages by epigenetic reprogramming

Abstract: Summary paragraphSexual reproduction ofToxoplasma gondii, which is restricted to the small intestine of felids, is sparsely documented, due to ethical concerns surrounding the use of cats as model organisms. Chromatin modifiers dictate the developmental fate of the parasite during its multistage life cycle, but their targeting to stage-specific cistromes is poorly described1. In this study, we found that transcription factors AP2XII-1 and AP2XI-2, expressed in tachyzoite stage that causes acute toxoplasmosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Pf EELM2 was previously predicted as a Pf MORC interactor (Hillier et al 2019) and identified in a quantitative histone peptide pulldown to be consistently recruited to H2B.Z_K13/14/18a (Hoeijmakers et al 2019). Furthermore, we also detected numerous ApiAP2 transcription factors [ Pf AP2-G5, Pf AP2-O5, Pf AP2-I, PF3D7_1107800, PF3D7_0613800, PF3D7_0420300 and PF3D7_1239200] ( Table 1 ), similar to results reported both by Hillier et al and with Toxoplasma Tg MORC complex (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). Pf AP2-G5 (PF3D7_1139300) and Pf AP2-O5 (PF3D7_1449500) were enriched 20.5- and 14.99-fold, respectively, suggesting that these factors are likely major components in-complex with Pf MORC.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Pf EELM2 was previously predicted as a Pf MORC interactor (Hillier et al 2019) and identified in a quantitative histone peptide pulldown to be consistently recruited to H2B.Z_K13/14/18a (Hoeijmakers et al 2019). Furthermore, we also detected numerous ApiAP2 transcription factors [ Pf AP2-G5, Pf AP2-O5, Pf AP2-I, PF3D7_1107800, PF3D7_0613800, PF3D7_0420300 and PF3D7_1239200] ( Table 1 ), similar to results reported both by Hillier et al and with Toxoplasma Tg MORC complex (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). Pf AP2-G5 (PF3D7_1139300) and Pf AP2-O5 (PF3D7_1449500) were enriched 20.5- and 14.99-fold, respectively, suggesting that these factors are likely major components in-complex with Pf MORC.…”
Section: Resultssupporting
confidence: 90%
“…Pf MORC association with chromatin remodelers has been shown (Bryant et al 2020), but how Pf MORC regulates gene expression in the asexual stage has not been evaluated. In T. gondii , the Tg MORC: Tg ApiAP2 complex acts as a transcriptional repressor of sexual commitment (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). This study found that Pf MORC co-immunoprecipitates with several chromatin remodeling proteins and many ApiAP2 transcription factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations